The Investigation of Phytochemical Contains, Antioxidant and Antimicrobial Activities of Malus floribunda Siebold ex Van Houtte From Eastern TURKEY - Kirbag, Sevda; Aydogan, Duygu (Assoc Pharmaceutical Teachers India, 2017)
Objective: M. floribunda is an ornamental and landscape plant in Turkey and it's small fruits are consumed as food. Antimicrobial, antioxidant activities and phytochemical contents of M. floribunda were investigated. Material and Method: M. floribunda was collected from different localities in the province of Elazig-Turkey. The nutritive value (flavonoid, sugar, fatty acid, vitamin, protein, element), antioxidant (lipid peroxidation, glutathione amounts and DPPH) and antimicrobial activities (on thirteen bacteria, three yeast and two dermatophyte) of M. floribunda were determined. Results: Vitamin (1.73-3.5 mu g/g A, 1.32-1.44 mu g/g D, 2.75-2.83 mu g/g E, 2.64-3.30 mu g/g K), flavonoid (33-253 mu g/g routine, 93-123 mu g/g morin, 0.22-0.32 mu g/g quercetin, 292-356 mu g/g naringenin), sugar (97-820 mu g/g), protein (1.4-1.6 mu g/g) and phytosterol (0.27-1.74 mu g/g ergosterol, 26-36 mu g/g stigmasterol, 95-121 mu g/g beta-sitosterol and 0.21-0.35 mu g/g retinol) levels can vary. In vitro medium, it is determined that in FeCl group, LPO amounts increases in a large ration with respect to the control group and LPO levels in groups which includes plant extracts and FeCl2, decreases in certain amounts. It was determined that the radical scavenging activity of the fruits increased due to the dose. Four different fatty acids were identified in the fruit. Fruits were found to different levels of sugar. Vitamin E in the examples were determined high rate. Protein found up to 1.686 mg/g. Ca content was the most detected in the all samples. Extracts inhibited the development of microorganisms at different rates. Conclusion Although studies on this type were limited, similarities and differences were seen in the results compared to other studies.
Keywords: M. Floribunda; Flavonoids; Phytosterol; Apple; Antioxidant Effect; Antimicrobial Activities